Pembentukan Portofolio Optimal dengan Menggunakan Teori Model Markowitz pada Perusahaan LQ-45 Terdaftar Bursa Efek Indonesia pada Tahun 2019 - Yudistira, Mochamad Dwiky; Mukaram (Jurnal Riset Bisnis dan Investasi, 2022)
This study is intended to see the direction, significance, and influence on portfolio return and risk on portfolio variance in LQ-45 companies in 2019. This study also aims to optimize portfolios based on the theory proposed by Markowitz which can be used as a reference for investors. The method used is descriptive quantitative with secondary data in the form of monthly share price data obtained from the information that has been collected. The population used that are included in the LQ-45 list in 2019. Then, multiple linear regression analysis and hypothesis testing are carried out with the f test and t test based on the calculated values ​​and table values ​​in each test which results in the conclusion that the return portfolio has a negative and significant effect, and risk has a positive and significant effect on portfolio variance with a significance level below 0.05